2019
DOI: 10.1186/s12984-019-0587-8
|View full text |Cite
|
Sign up to set email alerts
|

Learning and transfer of complex motor skills in virtual reality: a perspective review

Abstract: The development of more effective rehabilitative interventions requires a better understanding of how humans learn and transfer motor skills in real-world contexts. Presently, clinicians design interventions to promote skill learning by relying on evidence from experimental paradigms involving simple tasks, such as reaching for a target. While these tasks facilitate stringent hypothesis testing in laboratory settings, the results may not shed light on performance of more complex real-world skills. In this pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
167
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 94 publications
6
167
1
2
Order By: Relevance
“…p < 0.05 * addition to personal factors, task-related factors likely contribute to differences in motor skill acquisition and transfer from HMD-VR to conventional environments, and vice versa. Previous findings have suggested that fidelity and dimensionality influences the transfer of motor skills from HMD-VR environments [29]. In the current study, a possible explanation for the decrease in performance on a computer screen could be that the visual representation of the HMD-VR environment did not reflect what individuals expected and therefore, motor skill performance was not maintained with transfer.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…p < 0.05 * addition to personal factors, task-related factors likely contribute to differences in motor skill acquisition and transfer from HMD-VR to conventional environments, and vice versa. Previous findings have suggested that fidelity and dimensionality influences the transfer of motor skills from HMD-VR environments [29]. In the current study, a possible explanation for the decrease in performance on a computer screen could be that the visual representation of the HMD-VR environment did not reflect what individuals expected and therefore, motor skill performance was not maintained with transfer.…”
Section: Discussioncontrasting
confidence: 49%
“…One advantage of HMD-VR over conventional screen environments is the ability to realistically simulate the real world which allows for greater task specificity [27]. Task-related factors such as fidelity (i.e., imitation of the real environment) and dimensionality (i.e., matching dimensions between virtual and real environments) between HMD-VR and the real world have been shown to influence lower extremity motor performance [28] and have been suggested to have an influence on transfer in both lower and upper extremity motor transfer [29,30]. Individual differences in personal factors such as gender, age, video game experience, prior technical computer literacy, and computer efficacy seemed to influence transfer from HMD-VR to the real world in studies examining the transfer of spatial knowledge acquired in an HMD-VR environment [26,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is a real need to enhance transfer to make VR useful for rehabilitation and assistive technology applications [51, for review see 52]. Current thinking suggests that transfer should be enhanced the closer VR replicates the real-world [33,52]. The physical interactions in our EVR are generating accurate force, touch and proprioceptive perceptions which are lacking in conventional VR setups.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that our EVR framework could thus enhance learning and transfer between VR and the real-world. A recent review on learning and transfer in VR [52] also highlights the fidelity and dimensionality of the virtual environment as key components that determine learning and transfer, which are also addressed in our setup. In that sense, EVR mockup of real-life tasks, like the one presented here, should be the way forward as it addresses all the key components that determine learning and transfer in real-world tasks.…”
Section: Discussionmentioning
confidence: 99%